Validación de la prueba de memoria episódica de repetición de la Universidad del Sur de California (USC-REMT) - Rojas-Barahona,Cristian A (Sociedad Médica de Santiago, 2011)
Background: Memory is affected differently with the passage of time; specifically, episodic memory presents a clear decline. There is a relationship of this memory impairment and degenerative and psychiatric diseases. Aim: To determine the reliability and validity of the University of Southern California Repeatable Episodic Memory Test (USC-REMT) in a sample of Chilean adults. Material and Methods: The instrument was administered to 178 subjects living in the Metropolitan Region of Santiago. The sessions were individual, during the morning, lasting approximately 15 minutes. Results: The ANOVA indicates that subjects over 61 years old had lower scores in the test than their younger counterparts. There was an inverse correlation between age and success in "Free recall" (r =- 0.570), "Recognition indicating yes-no" (r = -0.412) and "forced-choice recognition" (r =- 0.371). Regression analysis showed that age explained 32.1 % "free recall" variance. The three components were grouped into a single factor. Conclusions: The USC-REMT meets the criteria for validity and reliability to be applied for clinical and research purposes.